PENGARUH KECEPATAN LANDING TERHADAP UMUR FATIK RANGKA TRICYCLE LANDING GEAR PESAWAT UAV MENGGUNAKAN ANSYS WORKBENCH - Lasinta Ari Nendra Wibawa (ELEMEN : JURNAL TEKNIK MESIN, 2020)
The landing gear is one crucial component in a UAV aircraft structure. Landing gear serves as the main supporting component of aircraft load when landing and take off. The paper aims to examine the effect of landing speed on the fatigue life of the tricycle landing gear of the UAV aircraft. The design of the tricycle landing gear frame uses Autodesk Inventor Professional 2017, while the analysis of fatigue life uses Ansys Workbench software. Landing speeds is varied 4 m/s, 6 m/s, 8 m/s, and 10 m/s. The fatigue life prediction using Gerber means stress theory with a fully-reserved type of loading. The landing gear material uses Aluminum alloy 6061. The simulation results show that the tricycle landing gear frame with landing speeds of 4, 6, 8, and 10 m/s has a minimum fatigue life of 1.00 x 108, 8.93 x 107, 4.30 x 106, 7.17 x 105 cycles. While the tricycle landing gear frame with landing speeds of 4, 6, 8, and 10 m/s has a minimum safety factor of 2.39, 1.59, 1.19, and 0.95. It means that the relationship between landing speed is inversely proportional to the fatigue life of the landing gear frame. The higher the landing speed, the lower the fatigue life of the landing gear frame. At a landing speed of 10 m/s, the landing gear frame fails to reach a minimum fatigue life of 1 million cycles.